The Social Ecology of Resilience A Handbook of Theory and Practice - Ungar, Michael; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
In a time of increasing exposure to personal psychological stress, as well as war, natural disasters, and economic upheaval, positive development under adversity$1 (Bresilience$1 (Bis meriting wider and deeper study. Despite this attention and over four decades$1 (Bworth of robust literature, resilience remains difficult to define and even harder to measure. Taking the view that resilience is a process to be developed and nurtured rather than a hard-wired capacity of the individual, The Social Ecology of Resilience explains how interactions with school, family, community, and culture can provide ingredients for positive development. Case studies representing international and cross-disciplinary perspectives (e.g., Aboriginal youth in Australia, refugees in Sudan, and gay teens in the U.S.) demonstrate resilience across cultures and the lifespan. And interviews with healers and activists who have themselves survived trauma reveal resilience as a set of processes that can be both learned and taught. Featured in the coverage: Causal pathways and how social ecologies influence resilience. Situating resilience in developmental contexts. Fostering recovery, sustainability, and growth in traumatized communities. Resources that promote resilient parenting. Children with disabilities and the supportive school. Indigenous perspectives on resilience. The up-to-date data and real-world viewpoints in The Social Ecology of Resilience will be of great interest to those working with this elusive concept, including social workers, psychologists, students and professors in family relations, and researchers in social policy.s
I. Introduction to the Theory -- Social Ecologies and their Contribution to Resilience -- Resilience: Causal Pathways and Social Ecology -- Theory and Measurement of Resilience: Views from Development -- Resilience and Children's Work in Brazil: Lesson from Physics for Psychology -- II. Five Interviews -- An Interview with Macalane Malindi: The Impact of Education and Changing Social Policy on Resilience During Apartheid and Post-Apartheid in South Africa -- An Interview with Bill Strickland: How Community-based Adult Educational Facilities can Lift People out of Poverty in Urban America -- An Interview with Jude Simpson: Growing Beyond a Life of Abuse and Gang Involvement in New Zealand -- An Interview with Vicki Durrant: Creating a Community Program for High-Risk Aboriginal Youth in Canada's North -- An Interview with Arn Chorn-Pond: Helping Children in Cambodia Through the Revival of Traditional Music and Art -- III. The Individual (in context) -- From Neurons to Social Context: Restoring Resilience as a Capacity for Good Survival -- Situating Resilience in Developmental Context -- Temporal and Contextual Dimensions to Individual Positive Development: A Developmental-Contextual Systems Model of Resilience -- Girls' Violence: Criminality or Resilience?- IV. The Family -- Facilitating Family Resilience: Relational Resources for Positive Youth Development in Conditions of Adversity -- Contexts of Vulnerability and Resilience: Childhood Maltreatment, Cognitive Functioning and Close Relationships -- Averting Child Maltreatment: Individual, Economic, Social and Community Resources that Promote Resilient Parenting -- Caring Relationships: How to Promote Resilience in Challenging Times -- Young People, Their Families and Social Supports: Understanding Resilience with Complexity Theory -- V. The School.-Local Resources and Distal Decisions: The Political Ecology of Resilience -- Caring Teachers: Teacher-youth Transactions to Promote Resilience -- Children with Disabilities and Supportive School Ecologies -- Resilience in Schools and Curriculum Design -- VI. The Community -- How Prior Social Ecologies Shape Family Resilience Amongst Refugees in U.S.Resettlement -- Young People, Sexual Orientation, and Resilience -- Community Resilience: Fostering Recovery, Sustainability, and Growth -- The Social Ecology of Resilience in War-Affected Youth: A Longitudinal Study from Sierra Leone -- Traveling Through Social Support and Youth Civic Action on a Journey Towards Resilience -- VII. Culture.-Understanding Culture and Resilience: The Production of Hope -- Case Study: Promoting Community Resilience with Local Values - Greenland's Paamiut Asasara -- Toward an Ecology of Stories: Indigenous Perspectives on Resilience -- Macro, Meso and Micro Perspectives of Resilience During and After Exposure to War -- Predictors of resilient psychosocial functioning in Western Australian Aboriginal Young People Exposed to High Family-level Risk.
Keywords: Social sciences; Psychotherapy; Social work; Psychology, clinical; Social Sciences; Social Work; Clinical Psychology; Psychotherapy